Evaluation of the effect of genetic selection on embryonic survival and nutritional supplementation on embryo survival as well as colostrum and milk composition and yield - Cilliers, Josephine Elizabeth (Stellenbosch : Stellenbosch University, 2025)
Thesis (MScAgric)--Stellenbosch University, 2024.